PERAN PASTORAL RAJA BIUS PADA KONFLIK SIGAPITON (MENILIK UPAYA BERTEOLOGI PASTORAL KOMUNAL KONTEKSTUAL DI SIGAPITON) - Robinson Simanungkalit (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThe theological paradigm is dynamic and that is the way it supposed to be. The theology we build must be contextual and transformative. By establishing such understanding, theological efforts can be done through every life event and can be used as a reflection of our theology. The conflict at Sigapiton has become a momentum for churches to have theology. The role of society and the ruler, raja bius, of Sigapiton must be seen critically as a theological effort by the community of the church’s congregations which have the dimension of communal and contextual pastoral care.Kata Kunci : Raja Bius, Konflik, Sigapiton, Paradigma, Teologi Pastoral, Komunal, Kontekstual.